Exploring Sociocultural Determinants and Resilience Mechanisms Among Young Married Couples in Rural Meratus, South Kalimantan - Mariani Mariani; Yusna Zaidah; Raihanah Abdullah; Muhammad Wahdini; Fauziah Hayati (Al-Ahkam, 2026)
This study examines the sociocultural determinants and mechanisms of family resilience among young couples in the Dayak Meratus community, South Kalimantan. Contrary to the global narrative that views early marriage as a structural vulnerability, this study demonstrates the existence of resilience mechanisms rooted in local culture. Using a qualitative phenomenological approach with 22 informants, data were collected through in-depth interviews, observation, and document analysis, and then analyzed thematically. The results indicate that institutionalized social practices such as arranged marriages, communal living patterns, land grants as initial economic capital, and minimal external intervention serve as social capital that strengthens family resilience. Resilience is determined not only by biological age but also by kinship support, cultural values, and the interaction between customary law, Islamic law, and state law. From the perspective of maqāṣid al-sharī‘a and ‘urf, these practices contribute to the protection of offspring, honor, and economic stability, although they still pose potential conflicts with marriage age regulations. This study emphasizes the importance of a contextual socio-legal approach in understanding the phenomenon of early marriage in Muslim indigenous communities.